Green autofluorescence of the index fingernails is a novel biomarker for noninvasive determinations on the status of tobacco smoking. Issue 12 (13th September 2022) - Zhang, Mingchao; Tao, Yue; Yu, Haibo; Wu, Danhong; Liao, Binhong; Qiu, Jian‐Ge; Jiang, Bing‐Hua; Ying, Weihai
Abstract: It is critical to discover novel biomarkers for tobacco smoking. Our study has indicated the green autofluorescence (AF) of Index Fingernails as a novel biomarker for rapid and noninvasive determinations on the status of tobacco smoking: The green AF intensity of the Index Fingernails of the smokers was remarkably higher than that of the nonsmokers in the natural populations. When the AF intensity of the Fingernails was used as the variable, the area under curve (AUC) for differentiating the smokers from the nonsmokers was 0.91. Similar results were obtained by analyzing the green AF of the Index Fingernails of the healthy populations and the patients of acute ischemic stroke. Collectively, our study has indicated the green AF of the Index Fingernails as a novel biomarker for tobacco smoking, based on which the first method for noninvasive, rapid and economical determinations on the status of tobacco smoking may be established. Abstract : It is highly valuable to discover novel biomarkers for tobacco smoking. Our study has indicated that the Index Fingernails' green autofluorescence (AF) may become a biomarker for rapid and noninvasive determinations on the status of tobacco smoking: Using the AF as variable, the areas under curve (AUC) for differentiating smokers from the nonsmokers was 0.916 and 0.914, respectively.